Czym jest stabilność polityczna państwa? - Trzciński, Krzysztof (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
Artykuł traktuje o problemie definiowania pojęcia „stabilność polityczna” państwa. Głównym jego celem jest odpowiedź na pytanie, co znaczy stwierdzenie, że dane państwo jest stabilne politycznie. Artykuł składa się z czterech części. W pierwszej wyjaśniany jest leksykalny sens słów: „stabilny”, „stabilność” i „stabilizacja”. W drugiej części analizowane jest rozumienie znaczenia terminu „stabilność polityczna” w piśmiennictwie politologicznym. Trzecia część artykułu poświęcona jest omówieniu kwantytatywnych prób ujmowania sensu pojęcia stabilności politycznej. W zakończeniu podjęta została próba zdefiniowania przedmiotowego terminu polegająca na syntezie elementów najczęściej spotykanych w propozycjach wyjaśniania istoty stabilności politycznej; oceniono związek między istnieniem stabilności politycznej a podstawowymi typami reżimu politycznego: demokracją i autorytaryzmem; oraz zidentyfikowano główne podejścia konceptualne w pojmowaniu przedmiotowego terminu.

This paper deals with the problem of defining the concept of the political stability of a state. Its aim is to answer the following question: What does the statement that ‘a given state is politically stable’ mean? The paper is composed of four parts. In the first one the meanings of the words: ‘stable,’ ‘stability’ and ‘stabilisation’ are explained. In the second part, the meaning of the term ‘political stability’ in political science literature is analysed. In the third part of the paper, quantitative attempts at formulating the sense of the concept of political stability are discussed. In conclusion, an attempt to arrive at a definition of the concept is made via a synthesis of the elements most frequently used in academic literature devoted to explaining the essence of political stability; the possible correlation between the existence of political stability and the principal types of political regime (democracy and authoritarianism) is evaluated; and the major conceptual approaches in understanding the term under consideration are identified.
What is the political stability of a state?
Keywords: stabilność polityczna; stabilny politycznie; niestabilność polityczna; niestabilny politycznie; państwo; political stability; politically stable; political instability; politically unstable; state